Razvoj dramatike Dušana Jovanovića - Borovnik, Silvija (Jezik in slovstvo, 2004)
Dušan Jovanović, whose dramatic opus has gone from Luddism and engaged political drama enwrapped into playful intertextuality and enclosed by sharp, gallows satire, developing into sensitive intimate playwriting and making a return to gallows humour, is one of the most expressive contemporary Slovene playwrights. According to research in literary history and criticism, the true value of his plays, written so that they can be added to and altered during their staging, is in the fact that they are a witty account of both the Slovene present and recent past. The article is an analysis of Jovanović's dramatic opus, focusing on the numerous novelties and idiosyncrasies of the playwright's poetics, which have influenced the development of Slovene playwrighting in the second half of the 20th century.
Keywords: Jovanović, Dušan, 1939-; Slovene literature; slovenska književnost; slovenska dramatika; literarne študije